What do Chilean and Costa Rican psychologists believe and advise about parenting? = ¿Qué creen y aconsejan psicólogos (as) chilenos (as) y costarricenses sobre la crianza de los (as) hijos (as) ? - Castro Carrasco, Pablo Javier
This research investigates the subjective theories of 12 Chilean and Costa Rican psychologists who work with children, with the purpose of describing and interpreting their explanations about child rearing. Episodic interviews wereused and analyzed using a Grounded Theory model. The interviewees point out that they use their own experience andbeliefs when advising parents. Results indicated that, according to the interviewees, the topics most frequently consulted byparents were children's high impulsivity and disciplining. The interviewees believe the most common parenting styles are theauthoritarian and the permissive ones, the latter being associated with parents' fear and anxiety.